Maximizing arthropod‐mediated ecosystem services in agricultural landscapes: the role of native plants. Issue 4 (26th August 2008) - Isaacs, Rufus; Tuell, Julianna; Fiedler, Anna; Gardiner, Mary; Landis, Doug
Abstract : Beneficial arthropods, including native bees, predators, and parasitoids, provide valuable ecosystem services worth $8 billion to US agriculture each year. These arthropod‐mediated ecosystem services (AMES) include crop pollination and pest control, which help to maintain agricultural productivity and reduce the need for pesticide inputs. Maximizing survival and reproduction of beneficial arthropods requires provision of pollen and nectar resources that are often scarce in modern agricultural landscapes. Increasingly, native plants are being evaluated for this purpose. Native plants can outperform recommended non‐natives and also provide local adaptation, habitat permanency, and support of native biodiversity. We predict that the success of insect conservation programs using flowering plants to increase AMES on farmland will depend on landscape context, with the greatest success in landscapes of moderate complexity. Reintegration of native plants into agricultural landscapes has the potential to support multiple conservation goals, and will require the collaboration of researchers, conservation educators, and native plant experts.